2019
DOI: 10.1021/acsphotonics.9b00820
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer Excitonic Emission for Imaging Spatial Dispersion of Photonic Crystals

Abstract: Spatial dispersion of a photonic crystal manifests itself as an angle dependent optical response. Here, we use the emerging two-dimensional transition metal dichalcogenides (TMDCs) as a photon source to directly image the spatial dispersion in the reciprocal space. Excitonic emission from a monolayer MoS 2 is coupled to the delocalized Fano resonances supported by the photonic crystal slab, recreating isofrequency contours in the far-field. This integration of monolayer TMDCs and photonic crystal not only reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Today, atomically thin two-dimensional layered materials (2DLMs) are at the focus of the optics and photonics community due to their unique optical and electrical properties. Therefore, this new generation of materials has led to a myriad of applications in science and nanotechnology, for instance, in the fields of nanophotonics and photovoltaics. Recently, the nonlinear optical response of several 2DLMs has been reported to be remarkably large. , In particular, inversion symmetry breaking and efficient light–matter interaction make transition-metal dichalcogenides (TMDs) an ideal platform to investigate nonlinear optics. , Several second- and third-order nonlinear parametric mechanisms, generated during monochromatic laser illumination, have been observed in a wide variety of TMDs, including MoS 2 , MoSe 2 , , MoTe 2 , WSe 2 , , WS 2 , , and ReS 2 . The study of nondegenerate parametric processes (i.e., involve several photon frequencies), such as sum-frequency generation (SFG) and four-wave mixing (FWM), is limited and has been shown in Mo-based and W-based , TMDs.…”
mentioning
confidence: 99%
“…Today, atomically thin two-dimensional layered materials (2DLMs) are at the focus of the optics and photonics community due to their unique optical and electrical properties. Therefore, this new generation of materials has led to a myriad of applications in science and nanotechnology, for instance, in the fields of nanophotonics and photovoltaics. Recently, the nonlinear optical response of several 2DLMs has been reported to be remarkably large. , In particular, inversion symmetry breaking and efficient light–matter interaction make transition-metal dichalcogenides (TMDs) an ideal platform to investigate nonlinear optics. , Several second- and third-order nonlinear parametric mechanisms, generated during monochromatic laser illumination, have been observed in a wide variety of TMDs, including MoS 2 , MoSe 2 , , MoTe 2 , WSe 2 , , WS 2 , , and ReS 2 . The study of nondegenerate parametric processes (i.e., involve several photon frequencies), such as sum-frequency generation (SFG) and four-wave mixing (FWM), is limited and has been shown in Mo-based and W-based , TMDs.…”
mentioning
confidence: 99%
“…With this in mind, we measured the overall PL far field emission pattern and only a bright light spot can be observed in the center of the Fourier plane (Figure c), indicating the purely unidirectional emission performance without extra azimuthally anisotropic PL residuals (Figure S4b). In contrast, other 2D exciton emission shaping methods based on PhCs and metasurfaces with square lattice usually suffer from azimuthally anisotropic PL residuals due to additional high order modes. , …”
Section: Resultsmentioning
confidence: 99%
“…As a result, the 2D excitons in the atomically thin TMDs lack emission directionality, which limits their practical applications in free space communications, optical sensors, optical microscopy, and so on. Recent progresses on dielectric photonic crystal (PhC) slabs and metasurfaces have shown that such photonic nanostructures can produce photonic modes with specific angular momentum dispersion, which can be utilized to effectively redistribute the excitonic angular emission of monolayer TMDs. , However, due to the low refractive index nature of conventional dielectric materials, these nanostructures usually require a large thickness to support the photonic modes, increasing the thickness of the entire device to hundreds of nanometers despite the atomically thin nature of the monolayer TMDs. , …”
mentioning
confidence: 99%
See 2 more Smart Citations